Post-exposure prophylaxis of COVID-19: results of double-blind, placebo-controlled, multicenter clinical study evaluation of efficacy and safety of double-stranded sodium salt RNA drug - L. A. Balykova; O. A. Radaeva; K. Ya. Zaslavskaya; A. V. Taganov; P. A. Bely; K. A. Zakharov; V. V. Popova; T. I. Chudinovskikh; S. V. Teplykh; I. V. Balaban; R. S. Kozlov; N. V. Kirichenko; et al. (Фармация и фармакология (Пятигорск))
The aim of the study was to evaluate the efficacy and safety of an RNA double-stranded sodium salt drug, a lyophilisate for a solution preparation for an intramuscular and subcutaneous administration, as a means of post-exposure COVID-19 prophylaxis in comparison with placebo.Material and methods. A double-blind, placebo-controlled, multicenter, randomized phase III clinical trial was conducted to evaluate the efficacy and safety of a double-stranded sodium salt RNA drug (RADAMIN®VIRO), a lyophilisate for preparing a solution for intramuscular and subcutaneous administration as a means of post-exposure prophylaxis of COVID-19. The study was conducted in 10 research centers in the Russian Federation from May 31, 2022 to January 17, 2023. The study included men and women aged ≥18 years who cohabitate with a person with a documented COVID-19 diagnosis and do not have symptoms characteristic of COVID-19. At the randomization stage, the subjects were assigned to one of two groups: group 1 (n=400) received a study drug RADAMIN®VIRO 5 mg (1 vial) intramuscularly once a day; group 2 (n=400) received placebo 1 vial intramuscularly once a day. The total duration of the study for each subject was no more than 30 days.Results. By day 10-11, in the double-stranded sodium salt RNA preparation group, the proportion of the subjects with confirmed COVID-19 and at least 1 symptom characteristic of COVID-19 was 5.76% (23/399), and in the placebo group – 11. 03% (44/399). The difference in proportions between the study drug and placebo groups was 0.0526 (5.26%), the 95% confidence interval (CI) for the difference in proportions between the groups was -95% CI [0.0123;0.0937]). More than 94% of single-dose subjects did not become infected with COVID-19 with any symptoms during the 11 days of the follow-up. As a result of a comparative analysis, it was shown that the infection frequency in the study drug group was statistically significantly (almost twice) less than in the comparison group, which indicates a high efficiency and expediency of using the double-stranded sodium salt RNA preparation as a means of the post-exposure COVID-19 prophylaxis.Conclusion. Thus, regardless of the vaccination availability, the effectiveness and feasibility of using the study double-stranded sodium salt RNA preparation as a means of the post-exposure COVID-19 prophylaxis was demonstrated not only in medical institutions (outpatient clinics and hospitals), but also in caregivers and/or the persons in contact with COVID-19 patients. The situation was the same in the organizations and enterprises in case of evolution of a mass infection threat and the availability of appropriate medical personnels.